Effects of Rumensin® ruminal delivery devices in grazing cattle on subsequent feedlot performance - Jack G. Riley; B. Cochran; Ronald V. Pope (Kansas Agricultural Experiment Station Research Reports, 1987)
Rumensin® Ruminal Delivery Devices put in place 76 days prior to steers entering a feedlot resulted in an average reduction in daily dry matter intake of 3.6% and a small 1.8% increase in daily gain during a controlled 28-day feeding phase. All steers were fed an 85% concentrate feedlot diet fortified with 30g/ton of Rumensin® and 10 g/ton of tylan®.
Keywords: Cattlemen& #x27; s Day; 1987; Kansas Agricultural Experiment Station contribution; no. 87-309-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 514; Beef; Rumensin®; Ruminal; Feedlot performance